The Impact of Kemal Atthatruk's Secularism on the Islamic World in the 19th Century. - Irwanti, Neneng; Pratama, Mohammd Ibrahim bayu (El Tarikh : Journal of History, Culture and Islamic Civilization, 2022)
The renewal of the Ottoman Empire was carried out by some groups from western education, aiming to strengthen domestic development through an effective strategy to maintain the territorial integrity of Turkey. The presence of Mustafa Kemal Ataturk was the beginning of progress as well as renewal in the Ottoman Empire which had long experienced collapse and destruction. In addition, his secular ideas made him the first leader to pioneer the westernization movement. With that Turkey became a modern country under the leadership of Kemal Atthatruk with military guard. In addition, he also made Muslims and interfaith tolerant in their religious practices. He also created a modern form of Islam by turning it into Islamic-oriented political parties. Therefore, this study aims to discuss the thoughts of secularism and the progress made by Kemal Ataturk as well as its impact on the Islamic world. To achieve this goal, in this study the author uses the historical method which is one way to solve a problem that originates in the past. By way of finding sources, verification, interpretation of sources and the last is historiography. As for obtaining sources, researchers used a type of library research which attempted to examine secularism and the progress initiated by Kemal Attatruk using a social approach.Kata Kunci: Sekularisme, Kemal Attratruk, Islam